2005
DOI: 10.1542/peds.2005-0026
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytic Sarcoma in a 3-Year-Old Male: A Case Report

Abstract: ABSTRACT. We describe a pediatric patient with histiocytic sarcoma involving the T6 and L4 vertebral bodies and the lungs. His tumor progressed during chemotherapy designed for Langerhans' cell histiocytosis and sarcoma. High-dose radiation, on the other hand, was effective. Pediatrics 2005;116:e322-e325. URL: www. pediatrics.org/cgi/doi/10.1542/peds.2005-0026; sarcoma, histiocytes, Langerhans' cell histiocytosis, histiocytic sarcoma.ABBREVIATIONS. LCH, Langerhans' cell histiocytosis; CT, computed tomography; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 18 publications
0
38
0
1
Order By: Relevance
“…In case of a multiple involvement of different sites, this systemic presentation is referred to as "malignant histiocytosis" [3]. HS arising in the lung has rarely been reported; indeed, only few well-documented reports of cases in humans exist [4,5]. According to the WHO, HS should be regarded as an aggressive haematopoetic neoplasm with a poor response to therapy being reflected by the study of Vos et al [6] who reported five cases of HS.…”
Section: Discussionmentioning
confidence: 99%
“…In case of a multiple involvement of different sites, this systemic presentation is referred to as "malignant histiocytosis" [3]. HS arising in the lung has rarely been reported; indeed, only few well-documented reports of cases in humans exist [4,5]. According to the WHO, HS should be regarded as an aggressive haematopoetic neoplasm with a poor response to therapy being reflected by the study of Vos et al [6] who reported five cases of HS.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha ubicado en diferentes sitios extraganglionares, que incluyen piel, pulmón, cavidad nasal, paladar, hueso, tracto gastrointestinal, bazo, hígado, tejidos blandos y sistema nervioso central [6][7][8][9][10][11][12] . El presente caso se suma a los previamente descritos en el tracto gastrointestinal, que incluyen localizaciones en el esófago 13 , estóma-go 14 , intestino delgado [6][7][8][15][16][17] , colon 8,9 , recto y ano 6 .…”
Section: Discussionunclassified
“…Only 3 cases of HS originating in the lung have previously been reported. 2,5,6 We encountered a young patient with HS of the lung containing spindle cells, mainly, and foam cells.…”
Section: Introductionmentioning
confidence: 99%